The receptor for advanced glycation end products (RAGE) sustains autophagy and limits apoptosis, promoting pancreatic tumor cell survival - Kang, Rui; Tang, D.; Schapiro, N. E.; Livesey, K. M.; Farkas, A.; Loughran, P.; Bierhaus, Angelika; Lotze, M. T.; Zeh, H. J. (Cell death and differentiation, 2010)
Activation of the induced receptor for advanced glycation end products (RAGE) leads to initiation of NF-κB and MAP kinase signaling pathways, resulting in propagation and perpetuation of inflammation. RAGE-knockout animals are less susceptible to acute inflammation and carcinogen-induced tumor development. We have reported that most forms of tumor cell death result in release of the RAGE ligand, high-mobility group protein 1 (HMGB1). We now report a novel role for RAGE in the tumor cell response to stress. Targeted knockdown of RAGE in the tumor cell, leads to increased apoptosis, diminished autophagy and decreased tumor cell survival . In contrast, overexpression of RAGE is associated with enhanced autophagy, diminished apoptosis and greater tumor cell viability. RAGE limits apoptosis through a p53-dependent mitochondrial pathway. Moreover, RAGE-sustained autophagy is associated with decreased phosphorylation of mammalian target of rapamycin (mTOR) and increased Beclin-1/VPS34 autophagosome formation. These findings show that the inflammatory receptor, RAGE, has a heretofore unrecognized role in the tumor cell response to stress. Furthermore, these studies establish a direct link between inflammatory mediators in the tumor microenvironment and resistance to programmed cell death. Our data suggest that targeted inhibition of RAGE or its ligands may serve as novel targets to enhance current cancer therapies.